(untitled) (Research, Society and Development, 2020)
Consumption of products and substances of plant origin is common practice in populations all over the planet. Morus nigra L. (blackberry) is a medicinal plant widely used in folk medicine, and has several active ingredients with therapeutic action, such as antioxidant, antinoceptive, hypoglycemic and anti-inflammatory activity. The aim of the present study was to analyze the possible cytotoxic, genotoxic and mutagenic activities of Morus nigra L. leaves through the Allium cepa test. For preparation of the extract were used blackberry leaves, collected in the city of Agricolândia-PI. Three different concentrations (0.007 mg / mL, 0.07 mg / mL and 0.7 mg / mL) were used, in addition to the negative and positive controls. For each extract concentration, 10 onion bulbs were used, which were exposed for germination. After growth, the roots were measured with the help of a ruler, cut and followed by the slide preparation procedure, which were visualized under a light microscope at 100x magnification and analyzed qualitatively for the presence of genetic damage. Statistical analysis was performed using the ANOVA system of mean sample results. After data analysis, it was observed that the size of root meristems indicated no toxicity, the mitotic indexes of A. cepa cells exposed at these concentrations were not statistically different from the negative control. The chromosomal aberrations found were not significant (P <0.05) in the concentrations used and micronuclei and binucleated cells did not show significant variations when compared to the negative control results. Thus, based on the results, the use of Morus nigra leaves is safe at the concentrations studied, but some studies can be performed to confirm the results and suggest greater reliability in the use of this plant by the population safely.